Consumption of Rabbiteye Blueberry Results in Accumulation of Hippuric Acid in the Bone Marrow and Increased Bone Deposition in Ovariectomized Rats but Few Other Bone Benefits (P06-064-19). (13th June 2019) - Maiz, Maria; Debelo, Hawi; Lachcik, Pamela; Lila, Mary; Bellido, Teresita; McCabe, George; Ferruzzi, Mario; Weaver, Connie
Abstract: Objectives: Determine the effects of an 8-wk chronic consumption of two different blueberry varieties at varying doses on calcium balance, calcium kinetics, bone microarchitecture and polyphenol metabolism and distribution in ovariectomized rats. Methods: Eighty 5-mo old ovariectomized rats were sorted by weight and block-randomized to an 8-wk chronic feeding treatment of a polyphenol-free (control), 2.5% or 5% `Montgomery ́ (Mont) rabbiteye blueberry ( V. ashei ) or 5% wild lowbush blueberry (Wild BB) ( V. angustifolium ) (% w/w). During week 0 and week 8, rats went through a calcium balance study to determine calcium absorption and retention. At the end of week 8, rats were dosed with 45 Ca and serial blood draws were done from baseline up to 48 h post-dose to map Ca kinetics. At sacrifice, the right femur was collected to determine differences in bone strength and microarchitecture of trabecular and cortical bone through MicroCT and a three-point bending test. A 24 h urine collection was done at baseline and during week 8 of treatment to determine urinary phenolic acid excretion and the left femur bone marrow phenolic acid accumulation through UPLC-MS/MS. Results: A blueberry enriched diet had no effect on cortical bone microarchitecture, with a trend towards increased trabecular bone protection (p = 0.08). No differences were observed in bone strength. During baseline, a 2.5% Mont diet significantly increased Ca retention, but the effect was lost after the 8 weeks of treatment when rats had stabilized to treatment. Calcium kinetics showed that Mont 5% significantly increased Ca absorption and bone turnover (p < 0.05), while Mont 2.5% and Wild BB 5% did not. An accumulation of hippuric acid in the bone marrow was detected with the Mont blueberry treatments and it was significantly and positively correlated with bone deposition. The metabolism of phenolic acids was significantly affected by a chronic consumption of the treatment diets, resulting in significant phenolic acid profiles and excretion shifts. Conclusions: A blueberry-enriched diet had minimal effects on bone after stabilized to ovariectomy and the effects differ depending on blueberry variety and dose. Funding Sources: National Institute of Health (NIH) and National Center for Complementary and Integrative Health (NCCIH).